Penyuluhan Dan Pemberantasan Sarang Nyamuk Serta Pelaksanaan Fogging Dalam Rangka Pencegahan Penyakit Demam Berdarah Dengue Di SMA Negeri 1 Berastagi - Perangin-angin, Susanti (PT. Cahya Edupreneur Indonesia, 2023)
Dengue hemorrhagic fever (DHF) is still one of the most important public health problems in Indonesia. Many efforts to control the disease have been carried out, such as larvaciding, fogging focus, and controlling mosquito breeding. This effort will be better if it involves community participation. The purpose of this community service activity is to provide knowledge to high school students about eradicating mosquito nests and preventing mosquito bites (Aedes aegypti) and implementing fogging in the context of preventing dengue. This community service is providing knowledge and implementing fogging at Berastagi 1 Public High School about eradicating mosquito nests and preventing mosquito bites (Aedes aegypti) in the context of preventing dengue. The results of this community service activity are by giving questionnaires before being given counseling about eradicating mosquito nests and preventing mosquito bites (Aedes aegypti) and implementing fogging in the context of preventing DHF to students of SMA Negeri 1 Berastagi and after being given counseling by providing material about DHF by providing a percentage of power point to students and also carried out Fogging activities (Fumigation) to eradicate adult mosquitoes. It is better if it can be implemented and used, namely in fostering the participation of school children who are continuously eradicating mosquito-transmitting mosquitoes by means of 3 M, namely: draining water reservoirs (TPA), closing TPA and burying/getting rid of used items that can collect rainwater. This method of prevention is also known as PSN (Eradication of Mosquito Nests). Efforts to motivate school children or the community to implement 3M continuously.